Aktiiviviljelijöiden tuotantoon ja toimeentuloon liittyvät suunnitelmat vuoteen 2002 - Ala-Orvola, Leena (Maatalouden taloudellinen tutkimuslaitos, 1998)
Maataloustuotantoa ainakin seuraavat viisi vuotta jatkavista tiloista peräti noin 40 % suunnittelee tuotannon laajentamista. Suurimmat tilat ovat eriytymässä tuotannon laajentajiksi, kun taas pienistä tiloista yhä useampi aikoo jatkaa tuotantoa entisessä laajuudessa. Vuosina 1996-1998 maataloustuotannon laajentajien osuus yli 50 peltohehtaarin tiloista kasvoi 41 prosentista 49 prosenttiin. Alle 20 peltohehtaarin tiloista laajentajien osuus puolestaan väheni 26 prosentista 17 prosenttiin. Vuosina 1996 - 1998 tilojen suunnitelmat investoida käyttöomaisuuteen ovat vähentyneet lukuun ottamatta uudisrakennusinvestointeja. Mm. kotieläintiloista 20 % suunnittelee edelleen kotieläinrakennuksen laajennusta tai uudisrakentamista ja 10 % peruskorjausta. Viljelijöiden arviot tilan ulkopuolisista lisäansiomahdollisuuksista ovat muuttuneet vuosi vuodelta myönteisemmiksi, ja myös tuloja hankkivien määrä on lisääntynyt. Tiloista 46 % hankkii tuloja perinteisen maatilatalouden ulkopuolelta, mikä on 6 %-yksikköä enemmän kuin kolme vuotta aikaisemmin. Yli 40 % tiloista hankkii satunnaisesti tai säännöllisesti palkkatyötuloja ja noin neljänneksellä tiloista harjoitetaan pienyritystoimintaa. Myös näillä laajennushalukkuus on erittäin korkea; pienyritystoiminnan osalta 44 % ja maatilan ulkopuolella työssä käyvien osalta 24 %. Kynnys aloittaa pienyritystoiminta tai palkkatyö on kuitenkin melko korkea, sillä vuosittain vain 3-5 % tiloista on ilmoittanut suunnittelevansa toiminnan aloittamista.

This study is concerned with the plans of active farms concerning their livelihood and production for 1998-2002 and changes in the plans for the next few years. The study is based on questionnaires sent in 1996-1998 to farms included in the profitability bookkeeping. There are about 1,050 bookkeeping farms located in different parts of the country and representing different production lines. Each year 67-75% of the farms returned the questionnaire sent in the beginning of the year. On full-time active farms the willingness to continue farming is very high. 10% of the farms are going to be transferred to a descendant within the next five years, and thus continuing the production seems quite well secured even if the current owners may be going to give up farming. 40% of the farms intend to expand agricultural production in the next five years. About a third of livestock farms plan to expand their production, but at the same time about 10% of farms intend to give up livestock production, which means that the average unit size is likely to grow quite rapidly. The average arable land area under cultivation has increased by about 2 ha per year, and at least the same rate of growth in the farm size can also be expected to occur in the future. In 1998 7% of the farms included in this study practised organic production, and this is about 1% more than in the previous year. 16% of the farms intend to expand their forestry activities in the near future, and plans concerning this were about as common in the previous years, too. An increasing number of farms has incomes from sources other than the traditional agriculture and forestry. On almost a half of the farms the farmer or spouse works full-time or part-time outside the farm. If farmers plans are realized, in 2002 there will be small-scale entrepreneurial activity on about 25% of livestock farms and about a third of crop producing farms. In general, however, small-scale entrepreneurial activities mainly bring additional incomes, and they do not provide an alternative to agriculture proper as the main source of income.
Plans of active concerning livelihood and production until 2002
Keywords: Ma; Suomi; maatalous; investoinnit; toimeentulo; tuotanto; agriculture; production; investments; livelihood; Finland